Pain control after thoracotomy. An extrapleural tunnel to provide a continuous bupivacaine infusion for intercostal nerve blockade. - Majid, A.A.; Hamzah, H. (1992)
This study was undertaken to determine whether an infusion of local anesthetic (LA) delivered through an extrapleural tunnel could provide satisfactory control of pain in the postthoracotomy period. Twelve patients undergoing thoracotomy were studied. A T-shaped tunnel was created by elevating the parietal pleura at the posteromedial end of the thoracotomy wound. An irrigation catheter was then inserted and an infusion of bupivacaine commenced, initially at 5 mg/kg/24 h and subsequently at 3 mg/kg/24 h. Pain was well controlled in eight patients and satisfactory in four patients. The latter required one dose of opiate analgesia each in the 48-h postoperative period. We conclude that an infusion of bupivacaine into the extrapleural space is an effective means of control of pain after thoracotomy.